The Influence of Leadership and Work Motivation on Employee Performance in the Non-Medical Section of Buah Hati Hospital, Ciputat, South Tangerang - Farida, Syarifah Ida; Zulkarnaen, Iskandar; Hidayat, Andriyan (International Journal of Social and Management Studies, 2022)
This study aims to examine the effect of leadership and work motivation on employee performance. Data were collected using a Likert scale questionnaire in March 2021 from 64 respondents, the sample objects were employees of the non-medical section of the Ciputat Fruit Hospital, South Tangerang, because they had characteristics that matched the variables to be studied. The collected data was tested by multiple regression method using SPSS 24.00. The result of this research is that leadership has no significant effect on employee performance. Work motivation has a significant effect on employee performance. Leadership and work motivation together have a significant effect on employee performance.